2015
DOI: 10.1007/s00205-015-0950-2
|View full text |Cite
|
Sign up to set email alerts
|

The Gross–Pitaevskii Hierarchy on General Rectangular Tori

Abstract: Abstract. In this work, we study the Gross-Pitaevskii hierarchy on general -rational and irrational-rectangular tori of dimension two and three. This is a system of infinitely many linear partial differential equations which arises in the rigorous derivation of the nonlinear Schrödinger equation. We prove a conditional uniqueness result for the hierarchy. In two dimensions, this result allows us to obtain a rigorous derivation of the defocusing cubic nonlinear Schrödinger equation from the dynamics of many-bod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…6 Later, Kirkpatrick, Schlein, and Staffilani [43] obtained the KM space-time bound via a simple trace theorem in both R 2 and T 2 and derived the 2D cubic defocusing NLS from the 2D quantum many-body dynamic. Such a scheme also motivated many works [11,13,18,20,35,38,57,58,61] for the uniqueness of GP hierarchies and enables the hierarchy method on the derivation 1D or 2D NLS directly from 3D [16,20,55], which is quite different but has some similar flavor with our Theorem 1.1 here. However, how to verify the KM bound in the 3D cubic case remained fully open at that time.…”
Section: Introductionmentioning
confidence: 77%
“…6 Later, Kirkpatrick, Schlein, and Staffilani [43] obtained the KM space-time bound via a simple trace theorem in both R 2 and T 2 and derived the 2D cubic defocusing NLS from the 2D quantum many-body dynamic. Such a scheme also motivated many works [11,13,18,20,35,38,57,58,61] for the uniqueness of GP hierarchies and enables the hierarchy method on the derivation 1D or 2D NLS directly from 3D [16,20,55], which is quite different but has some similar flavor with our Theorem 1.1 here. However, how to verify the KM bound in the 3D cubic case remained fully open at that time.…”
Section: Introductionmentioning
confidence: 77%
“…Around the same time, Gressman, Sohinger and Staffilani [32] studied the uniqueness of equation (1.2) in the T 3 setting and found that the sharp collapsing estimate on T 3 needs 𝜀 more derivatives than the R 3 case, in which one derivative is needed. Herr and Sohinger later generalised this fact to all dimensions [34] -that is, collapsing estimates on T 𝑛 always need 𝜀 more derivatives than the R 𝑛 case proved in [16]. 8 In 2013, T. Chen, Hainzl, Pavlović and Seiringer introduced the quantum de Finetti theorem, from [51], to the derivation of the time-dependent power-type NLS and provided, in [6], a simplified proof of the R 3 unconditional uniqueness theorem regarding equation (1.2) from [29].…”
Section: Forum Of Mathematics Pimentioning
confidence: 90%
“…Around the same time, Gressman, Sohinger and Staffilani [32] studied the uniqueness of equation (1.2) in the setting and found that the sharp collapsing estimate on needs more derivatives than the case, in which one derivative is needed. Herr and Sohinger later generalised this fact to all dimensions [34] – that is, collapsing estimates on always need more derivatives than the case proved in [16]. 8…”
Section: Introductionmentioning
confidence: 99%
“…Around the same period of time, Gressman, Sohinger, and Staffilani [29] studied the uniqueness of the GP hierarchy on T 3 and proved that the sharp space-time estimate on T 3 needed an additional ε derivatives than the R 3 setting in which one derivative is needed. Later, Herr and Sohinger generalized this fact to more general cases in [32].…”
Section: Introductionmentioning
confidence: 90%